Nomophobia Tendency in College Students Who Have Extroverted Per-sonalities - Ananda Pratiwi; IGAA Noviekayati; Niken Titi Pratitis (Eduvest - Journal of Universal Studies, 2025)
Although previous research has examined the general impact of nomophobia—anxiety experienced when without a mobile phone—on student populations, limited studies have specifically addressed how this condition manifests among individuals with extroverted personalities. This study aims to fill that gap by descriptive analysis of nomophobia tendencies in college students who identify as extroverts. Utilizing a quantitative descriptive approach, data were collected through purposive sampling from 148 students aged 18–25 years. The findings revealed that 127 out of 148 extroverted students demonstrated a notable tendency toward nomophobia. These results highlight the significant vulnerability of extroverted individuals to mobile phone dependence, likely due to their high need for social interaction. The study contributes to psychological research by underscoring the intersection between personality traits and technology-related anxiety. Practically, the findings offer valuable insight for mental health professionals and educators to develop targeted interventions for reducing nomophobia in extroverted student populations.